DEVELOPMENT OF FLIPBOOK-BASED SCIENCE HANDOUTS WITH AN SDGS AND LOCAL WISDOM APPROACH TO ENHANCE HIGHER ORDER THINKING SKILLS OF PGSD STUDENTS - Syaifani; Sari, Siti Mayang; Iqbal, Muhammad; Jalaluddin (International Journal of Cultural and Social Science, 2026)
A handout is a written instructional material organized in a concise and systematic manner to assist students in understanding learning content. The use of flipbook-based science handouts can enhance Higher Order Thinking Skills (HOTS) because the visual presentation of the material and flexible navigation enables students to explore science concepts in depth, connect SDGs-based theories with local wisdom phenomena, and increase active engagement as well as independent learning. This study employed a Research and Development (R&D) method using the ADDIE development model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research technique used purposive sampling with a sample of 30 PGSD students at Universitas Serambi Mekkah. Data collection instruments included expert validation sheets, response questionnaires, and HOTS tests in the form of pretests and posttests. The results showed that the average pretest score was 71 and increased to 96 in the posttest. The improvement in students’ HOTS was indicated by an average N-Gain score of 0.86 and an N-Gain percentage of 86.05%, which falls into the high category. The practicality test results showed that both student and lecturer responses were categorized as very practical. Therefore, the flipbook-based science handout with an SDGs and local wisdom approach is valid, practical, and effective in improving the HOTS of PGSD students.